The susceptibility of silver crucian carp (Carassius auratus langsdorfii) to infection with koi herpesvirus (KHV). Issue 10 (25th July 2019) - Kim, Hyoung Jun; Kwon, Se Ryun; Olesen, Niels Jørgen; Yuasa, Kei
Abstract: Koi herpesvirus (KHV) infections cause high mortality in carp ( Cyprinus carpio ). This study compared the susceptibility of silver crucian carp ( Carassius auratus langsdorfii ), also called ginbuna, and koi carp to KHV infection. Silver crucian carp and koi carp were challenged with KHV by both intraperitoneal injection and immersion, respectively, and kept in tanks at 22°C. All KHV‐exposed koi carp died within 14 days post‐infection (dpi), whereas no clinics nor mortality was observed in the KHV‐exposed silver crucian carp. KHV DNA was detected in both koi and silver crucian carp shortly after infection. At 7 dpi, the copy numbers of KHV genome were increased in koi carp but decreased in silver crucian carp. Using reverse transcriptase PCR, KHV mRNA was detected in koi carp but not in silver crucian carp. Cell cultivation on common carp brain (CCB) cell samples from koi carp caused KHV‐associated cytopathic effects in CCB cells. Therefore, we concluded that KHV replicated in koi carp but not in silver crucian carp and that silver crucian carp is not susceptible to infection with KHV.